Innovating the Pesantren Curriculum Toward a Structured Tahfizhul Qur’an Program: A Case Study at Darussalamah Al Mubarok Islamic Boarding School, Cianjur (Lembaga Pengembangan Kinerja Dosen, 2025)
Social changes and the demands of the times have encouraged Islamic boarding schools (pesantren) to continuously innovate in curriculum development. This article describes the outcomes of two workshops held at Pondok Pesantren Darussalamah Al Mubarok Cianjur, focusing on needs analysis, formulation of innovation objectives, implementation, and evaluation of a Tahfizhul Qur’an-based curriculum. The first workshop emphasized needs analysis and innovation design, while the second focused on implementation and evaluation. The results show that the curriculum shift toward a Tahfizhul Qur’an orientation received positive responses from all pesantren stakeholders, and both the implementation framework and evaluation system have been designed. This activity underscores the importance of a participatory and needs-based approach in pesantren curriculum development.